2007
DOI: 10.1186/bcr1749
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer is a promising target for vaccination using cancer-testis antigens known to elicit immune responses

Abstract: Introduction Cancer-testis antigens (CTAGs) are expressed solely in germ cells and in malignant tissues. They are targets of immune responses mediated by cytotoxic T cells in some cancers, and there is much interest in developing vaccines that induce these responses. The purpose of the present study was to ascertain the frequency of expression of CTAGs in breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…CTAs are involved in cellular proliferation, migration/motility, colonization, and cell division in normal germ cells, while in cancer cells, CTAs have been implicated in sustenance of growth, maintaining nutrient and oxygen supply through the activation of angiogenesis, evading apoptotic cell death, increase in tissue invasiveness and metastasis, and development of resistance to anti-cancer drugs [214]. In breast cancer, CTAs, such as MAGE-1, AKAP4, NY-BR-1, CTAG1, BAGE1, MAGE-A10, SP17, NY-ESO-1, and MAGE-A, were found to play important roles in activating cell proliferation, inhibition of apoptosis, and promoting tissue invasion and metastasis [5,[215][216][217][218][219][220][221][222]. The CTA, AKAP4, in particular seems to be an interesting candidate for a serum-based diagnostic test for the early detection and diagnosis of breast cancer [221].…”
Section: Metformin and Breast Cancer Biomarkersmentioning
confidence: 99%
“…CTAs are involved in cellular proliferation, migration/motility, colonization, and cell division in normal germ cells, while in cancer cells, CTAs have been implicated in sustenance of growth, maintaining nutrient and oxygen supply through the activation of angiogenesis, evading apoptotic cell death, increase in tissue invasiveness and metastasis, and development of resistance to anti-cancer drugs [214]. In breast cancer, CTAs, such as MAGE-1, AKAP4, NY-BR-1, CTAG1, BAGE1, MAGE-A10, SP17, NY-ESO-1, and MAGE-A, were found to play important roles in activating cell proliferation, inhibition of apoptosis, and promoting tissue invasion and metastasis [5,[215][216][217][218][219][220][221][222]. The CTA, AKAP4, in particular seems to be an interesting candidate for a serum-based diagnostic test for the early detection and diagnosis of breast cancer [221].…”
Section: Metformin and Breast Cancer Biomarkersmentioning
confidence: 99%
“…Although our lack of knowledge about the biological function of CTAs complicates their utilisation, the use of CTAs as targets for the vaccination of breast cancer has been under debate widely the last years [41]. …”
Section: Discussionmentioning
confidence: 99%
“…Another CTA, NY-BR-1 was frequently observed in breast cancers, indicating a possibility to define new targets in breast cancer based on NY-BR-1 [210]. Taylor et al has reported that, a vaccine directed against three CTAs-CTAG1, BAGE1 and MAGE-A10, can target two-thirds of breast cancers and can specifically target cytotoxic-T-lymphocyte responses [211]. Within the more stubborn TNBCs, when compared to other forms of breast cancer, CTA -SP17 is expressed in TNBCs [212].…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…Additionally, MAGE-A and NY-ESO-1 was reported to be expressed in a large population of TNBCs, thereby making MAGE-A and NY-ESO-1 potential targets for the development of vaccines [215]. The frequent occurrence of specific CTAs in breast cancers indicate a possibility to define and include new targets for therapeutic intervention [210,211]. Certain CTAs were expressed in the more stubborn TNBCs [212][213][214][215].…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%